Manual de procedimientos del departamento de Prensa y Relaciones Públicas del ICODER - García-Jarrett, Alejandro (Instituto Tecnológico de Costa Rica., 2016)
The objective of this work was to prepare a proceeding handbook for the Press and Public Relations Department, based on the premises of the Costa Rican Institute of Sport and Recreation (ICODER). This project is important because a proceeding manual is a useful tool for both, private or governmental organizations. For this project, the issues and the current conditions of the Press and Public Relations Department were identified. It was found that this Department did not have a handbook describing those tasks about the staff´s responsibilities. Therefore, based on that detected necessity, it was prepared a handbook, in order to achieve the department´s objectives. A qualitative research was done with a descriptive scope. It was also studied the current situation of this department, as well as those relevant processes related to the preparation of a handbook. Some primary sources were used to collect data, as questionnaires, personal interviews, observations and review of different documents. An analysis of procedures and forms was lead, afterwards the conclusions and recommendations were offered
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2016.
Keywords: Instituto Costarricense del Deporte y la Recreación; Manuales de procedimientos; Análisis administrativo